Apelin attenuates depressive-like behavior and neuroinflammation in rats co-treated with chronic stress and lipopolysaccharide. (October 2019) - Zhang, Zi-xuan; Li, E.; Yan, Jian-ping; Fu, Wan; Shen, Pei; Tian, Shao-Wen; You, Yong
Abstract: Several experimental studies have proved that activation of neuroinflammation pathways may contribute to the development of depression, a neuropsychiatric disorder disease. Our previous studies have shown the antidepressant properties of apelin, but the mechanism was unkown. This study was performed to verify whether the antidepressant effect of apelin was related to its anti-inflammation effect in the central nervous system. To achieve our aim, we selected the co-treatment of chronic stress and LPS to induced an inflammatory process in rats. The effect of this co-treatment was evaluated through the expression of inflammatory markers and glial cell activation. LPS injection co-treated with unpredictable chronic mild stress resulted in the activation of microglial cell and astrocyte, expression of inflammatory markers and depressive behaviors. Treatment with apelin significantly attenuates the deleterious effects in these rats. Our results showed that apelin improved depressive phenotype and decreased the activation of glial cells in stress co-treatment group. The down-regulations of p-NF-κB and p-IKKβ suggested that the effects are possibly mediated by inhibition of the NF-κB-mediated inflammatory response. These findings speculated that intracerebroventricular injection of apelin could be a therapeutic approach for the treatment of depression, and the antidepressant function of apelin may closely associated with its alleviation in neuroinflammation. Highlights: Apelin-13 reverses the depressive phenotype in rats co-treated with chronic stress and LPS. Apelin-13 decreases the activation of glial cells in a stress model Apelin-13 decreases the expression of inflammatory mediators in the hippocamspus of stressed rats. Apelin-13 inhibits inflammatory signaling pathways in the hippocamspus of stressed rats.